Knowledge Domain and Hotspots Predict Concerning Electroactive Biomaterials Applied in Tissue Engineering: A Bibliometric and Visualized Analysis From 2011 to 2021 - Xiong, Wentao; Wang, Sheng; Wei, Ziheng; Cai, Yibo; Li, Bo; Lin, Feng; Xia, Demeng (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Electroactive biomaterials used in tissue engineering have been extensively studied. Electroactive biomaterials have unique potential advantages in cell culture and tissue regeneration, which have attracted the attention of medical researchers worldwide. Therefore, it’s important to understand the global scientific output regarding this topic. An analysis of publications on electroactive biomaterials used in tissue engineering over the past decade was performed, and the results were summarised to track the current hotspots and highlight future directions. Methods: Globally relevant publications on electroactive biomaterials used in tissue engineering between 2011 and 2021 were extracted from the Web of Science database. The VOSviewer software and CiteSpace were employed to visualise and predict trends in research on the topic. Results: A total of 3,374 publications were screened. China contributed the largest number of publications (995) and citations (1581.95, actual value ×0.05). The United States achieved the highest H-index (440 actual values ×0.05). The journal Materials Science & Engineering C-materials for Biological Applications (IF=7.328) published the most studies on this topic (150). The Chinese Academy of Science had the largest number of publications (107) among all institutions. The publication titled Nanotechnological strategies for engineering complex tissues by Dir, T of the U.S. had the highest citation frequency (985 times). Regarding the function of electroactive materials, the keyword “sensors” emerged in recent years. Regarding the characterisation of electroactive materials, the keyword “water contact angle” appeared lately. Regarding electroactive materials in nerve and cardiac tissue engineering, the keywords “silk fibroin and conductive hydrogel” appeared recently. Regarding the application of electroactive materials in bone tissue engineering, the keyword “angiogenesis” emerged in recent years. The current research trend indicates that although new functional materials are constantly being developed, attention should also be paid to their application and transformation in tissue engineering. Conclusion: The number of publications on electroactive biomaterials used in tissue engineering is expected to increase in the future. Topics like sensors, water contact angle, angiogenesis, silk fibroin, and conductive hydrogels are expected to be the focuses of research in future; attention should also be paid to the application and transformation of electroactive materials, particularly bone tissue engineering.